LEVERAGE, DEBT MATURITY AND CORPORATE PERFORMANCE: EVIDENCE FROM CHINESE LISTED COMPANIES - Vijayakumaran, R.; Vijayakumaran, S. (Asian Economic and Financial Review, 2019)
This paper examines the relationship between leverage, debt maturity and firm performance, employing a large panel of Chinese non-financial listed firms. The corporate finance literature widely recognizes that the debt and maturity structures are important mechanisms for addressing agency problems in modern corporations. We applied the system GMM estimator to control for endogeneity concerns in the study. We found positive associations between leverage and the proportion of long term debt, and between leverage and firm performance. Our results indicate that leverage and its maturity structure are important determinants of the profitability of Chinese listed firms. Our research has significant policy implications as it suggests that, since China's financial system is dominated by a large banking system, lenders (mainly banks) may extend more long term credit to the more productive private sector, which helps to improve performance of these firms. The findings of this study imply that the Chinese government’s efforts to improve the governance of its banking system have been successful in enhancing efficiency and prudence in banks’ lending and monitoring behavior.
Keywords: Debt maturity; Bank financing